LoRa Throughput Analysis With Imperfect Spreading Factor Orthogonality - Waret, Antoine; Kaneko, Megumi; Guitton, Alexandre; El Rachkidy, Nancy (IEEE wireless communications letters, 2019)
LoRa is one of the promising techniques for enabling low power wide area networks for future Internet-of-Things devices. Although LoRa allows flexible adaptations of coverage and data rates, it is subject to intrinsic types of interferences: co-SF interferences due to collisions among end-devices with the same spreading factor (SF), and inter-SF interferences due to collisions among devices with different SFs. Most current works have considered perfect orthogonality among different SFs. We thus provide a theoretical analysis of the achievable LoRa throughput in uplink, where all LoRa-specific capture conditions are included. Results show the accuracy of our analysis despite approximations, and the throughput losses from imperfect SF orthogonality, under different SF allocations. Our analysis will enable the design of specific SF allocation mechanisms, in view of further throughput enhancements.